The Function of the Rule of La-Ḍarar in Islamic Rulings on Animal Treatment - Mohammad Shafiei (پژوهش‌های فقهی مسائل مستحدثه, 2024)
Despite the frequent and important instances of the rule of no harm (la darar) in the interactions of modern humans with animals, this rule has rarely been considered in jurisprudential research on animal behavior. Islamic research on how to interact with animals will both pave the way for the enactment of related laws and, at the stage of implementing these laws, will provide religious enforcement for the religious community. The purpose of this research, which is written in a descriptive-analytical method, is to state the instances of no harm and analyze the quality of the application of this rule in the rulings of dealing with animals. To this end, in the first step, the most important اصولی differences of opinion about the rule of no harm and their impact on the principle and method of selecting instances of the rule are stated; In the second step, after explaining the points that need to be considered in applying no harm to environmental instances, the most important instances of this rule in dealing with animals are examined.